A Dynamic and Cooperative Control Strategy for Multi-Hybrid Energy Storage System of DC Microgrid Based on SOC - Li, Hao; Fu, Lijun; Zhang, Yan; Xiong, Yiyong (Frontiers in Energy Research, 2022)
With the increasingly serious crisis of fossil energy and environmental pollution, clean renewable energy becomes the inevitable choice of energy structure adjustment. The instability of output power of distributed renewable energy system greatly affects the operation of DC microgrid. The hybrid energy storage system (HESS) composed of High-Energy Battery (HEB) and High-Power Battery (HPB) can solve the above problems. Thus, this paper proposes a dynamic and cooperative control strategy for multi-HESS based on state of charge (SOC). Based on the traditional LPF method and droop control, this paper proposes a control strategy that requires no communication among multiple hybrid energy storage (HES) modules. This method can realize the stable control of HEB current, reduce the change times of HEB charging-discharging mode, prevent HEB from overcharging and overdischarging, prolong the service life of HEB and balance different energy storage SOC, so as to improve the operation stability and economy of DC microgrid. In addition, the method has certain robustness against sudden failures. Simulation and experiment results show the effectiveness of the proposed method.